Influence of artificial sebum on the dermal absorption of chemicals in excised human skin: A proof-of-concept study. (June 2016) - Schneider, Désirée; Dennerlein, Kathrin; Göen, Thomas; Schaller, Karl Heinz; Drexler, Hans; Korinth, Gintautas
Abstract: In an initial diffusion cell study, the influence of artificial sebum on dermal penetration and intradermal reservoir of ethanol and toluene was investigated in comparison with the effects of a skin cream (o/w- and w/o-emulsion) and untreated (control) skin. Human skin was exposed to neat ethanol and toluene for 4 h, respectively. During the experiments, the penetration of the compounds was assessed in the receptor fluid. The amounts of the test compounds in the skin were determined at the end of exposure. In the control experiments, 42% of the total resorbed ethanol amounts were found in the intradermal reservoir after 4 h, whereas 82% of the toluene amounts were found in the skin compartments. The treatment with artificial sebum showed no significant differences in dermal absorption of both test compounds compared to control skin. In contrast, the treatment with skin cream increased the percutaneous penetration (p < 0.001) and the intradermal reservoir of ethanol ~ 2-fold but not of toluene. In all exposure scenarios, a relevant intradermal reservoir was formed. The results indicate that sebum does not influence the percutaneous penetration and the intradermal reservoir of epidermally applied chemicals, whereas the application of skin creams may increase the dermal penetration of the compounds. Highlights: The influence of artificial sebum and skin cream on the penetration of ethanol and toluene was investigated in human skin. Sebum does not enhance the dermal penetration and the intradermal reservoir of the solvents ethanol and toluene. Application of skin cream increases the penetration of ethanol. The removal of sebum by surgical disinfection seems not to be challenging the use of human skin for ex vivo experiments.